(S)-Erypoegin K, an isoflavone isolated from Erythrina poeppigiana, is a novel inhibitor of topoisomerase IIα: Induction of G2 phase arrest in human gastric cancer cells. (15th January 2021) - Hikita, Kiyomi; Yamakage, Yuko; Okunaga, Honoka; Motoyama, Yui; Matsuyama, Haruka; Matsuoka, Kenta; Murata, Tomiyasu; Nakayoshi, Tomoki; Oda, Akifumi; Kato, Kuniki; Tanaka, Hitoshi; Asao, Naoki; et al.
Graphical abstract: Highlights: Target molecule of ( S )-erypoegin K was identified to be topoisomerase II. ( S )-erypoegin K inhibited enzyme activity of purified human topoisomerase II. Docking study revealed the specific binding of ( S )-erypoegin K to the enzyme. ( S )-erypoegin K induced potent G2 phase arrest in the cell cycle. ( S )-erypoegin K exhibited antitumor activity both in vitro and in vivo . Abstract: Erypoegin K, an isoflavone isolated from the stem bark of Erythrina poeppigiana, has a single chiral carbon in its structure and exists naturally as a racemic mixture. Our previous study showed ( S )-erypoegin K selectively exhibits potent anti-proliferative and apoptosis-inducing activity against human leukemia HL-60 cells. To identify the target molecule of ( S )-erypoegin K, we employed the human cancer cell panel analysis (termed JFCR39) coupled with a drug sensitivity database of pharmacologically well-characterized drugs for comparison using the COMPARE algorithm. ( S )-erypoegin K exhibited a similar profile to that of etoposide, suggesting the molecular target for erypoegin K may be topoisomerase II (Topo II). Subsequent experiments using purified human Topo IIα established that the ( S )-isomer selectively stabilizes the cleavage complex composed of double-stranded plasmid DNA and the enzyme. Moreover, ( S )-erypoegin K inhibited decatenation of kinetoplast DNA. Molecular docking studies clearly indicated specific binding of the ( S )-isomer to the active site of Topo IIα involving hydrogen bonds that help stabilize the cleavage complex. ( S )-erypoegin K displayed potent cytotoxic activity against two human gastric cancer cells GCIY and MKN-1 with IC50 values of 0.270 and 0.327 μM, respectively, and induced enzyme activities of caspase 3 and 9. Cell cycle analysis showed marked cell cycle arrest at G2 phase in both cell lines. ( S )-erypoegin K also displayed significant antitumor activity toward GCIY xenografted mice. The present study suggests ( S )-erypoegin K acts as a Topo II inhibitor to block the G2/M transition of cancer cells.